2014
DOI: 10.4271/2014-01-1182
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Piston Heat Transfer in a Light Duty Engine Under Conventional Diesel, Homogeneous Charge Compression Ignition, and Reactivity Controlled Compression Ignition Combustion Regimes

Abstract: An experimental study has been conducted to provide insight into heat transfer to the piston of a light-duty single-cylinder research engine under Conventional Diesel (CDC), Homogeneous Charge Compression Ignition (HCCI), and Reactivity Controlled Compression Ignition (RCCI) combustion regimes. Two fast-response surface thermocouples embedded in the piston top measured transient temperature. A commercial wireless telemetry system was used to transmit thermocouple signals from the moving piston. A detailed comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…2,28 Since this study primarily focuses on heat transfer in a light-duty engine operated at lightto-medium loads where soot emissions are low and combustion temperature is relatively low, it is expected that ignoring the radiation heat transfer will not significantly affect the final predictions. Furthermore, in the deviation of equation (11), the contributions due to unsteadiness, the rate of pressure rise (dp=dt), and chemical energy release ( _ q c ) in the thermal boundary layer were ignored. The introduction of the quasi-steady assumption is based on the finding of Han and Reitz, 12 who indicated that the effect of unsteadiness on wall heat flux is insignificant.…”
Section: Heat Transfer Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…2,28 Since this study primarily focuses on heat transfer in a light-duty engine operated at lightto-medium loads where soot emissions are low and combustion temperature is relatively low, it is expected that ignoring the radiation heat transfer will not significantly affect the final predictions. Furthermore, in the deviation of equation (11), the contributions due to unsteadiness, the rate of pressure rise (dp=dt), and chemical energy release ( _ q c ) in the thermal boundary layer were ignored. The introduction of the quasi-steady assumption is based on the finding of Han and Reitz, 12 who indicated that the effect of unsteadiness on wall heat flux is insignificant.…”
Section: Heat Transfer Modelmentioning
confidence: 99%
“…Based on the measurements of surface temperature, the surface heat flux was calculated by utilizing Fourier analysis. More about the experimental setup can be found in Gingrich et al 11 To save computational time, a 1/7th sector mesh was employed for the simulations, which corresponds to the 7-hole injector used in this study. Figure 1 shows the computational domain and grid.…”
Section: Engine Specificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation. Temperature field and heat transfer coefficient are important boundary conditions for the piston thermal analysis [19,20]. The third type of boundary condition is usually adopted in the analysis of the piston, which requires the temperature T and heat transfer coefficient α of the peripheral medium to be given.…”
Section: Temperature Field Measurement and Numericalmentioning
confidence: 99%
“…The benefit of reduced heat loss with greater effective expansion ratio has been demonstrated only in low-temperature combustion (LTC) concepts such as Partially Pre-mixed Compression Ignition (PPCI) or Reactivity Controlled Compression Ignition (RCCI). The heat flux to the walls has been shown to decrease with retarded combustion in LTC engines as well [4], and hence a DCEE with LTC would be very beneficial. The low-temperature combustion concepts have been successfully demonstrated in labs and demonstration vehicles but lack the required controls has stopped to their adoption in production vehicles.…”
Section: Double Compression Expansion Enginementioning
confidence: 99%